PENGEMBANGAN E-BOOK PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Desi Eka Pratiwi (JIPD (Jurnal Inovasi Pendidikan Dasar), 2024)
A teacher needs the right strategy to build a conducive and enjoyable learning atmosphere for his students. The purpose of this research is to develop e-book learning resources that are interesting and in accordance with the characteristics of elementary school students. This type of research is development research that was developed using the ADDIE model which consists of five steps, namely Analyze, Design, Develop, Implementation, and Evaluation. Data collection techniques using tests and questionnaires. Researchers involved two validators to validate the e-book and the material contained in the e-book. Based on the validation results, it shows that (1) the e-book developed by the researcher is included in the valid/feasible category with an achievement of 91.25%. (2) The material in the e-book is proven to be effective and in accordance with the characteristics of students at the elementary school level with a score of 97.5% included in the valid qualification (3) The student response questionnaire shows that the use of the e-book is proven to be effective and easy to understand with the results of student responses by 91.1%. Based on the acquisition of values ​​in the data analysis above, it can be concluded that the basis for the development of e-book media in thematic learning is valid/fit for use in elementary schools. Keywords: E-Book, Thematic Learning, Elementary School